The effects of workplace spirituality towards organizational commitment among employees a development bank of Malaysia / Muhamad Khalil Omar … [et al.] - Omar, Muhamad Khalil; Che Mamat, Rusalbiah; Amirrudin, Faizatul Akmam; Nordi, Nurul Asyiqin (Faculty of Accountancy, 2019)
The main objective of this research is to determine the effects of workplace spirituality towards organizational commitment in one of main development bank in Malaysia. In this study the dimensions of workplace spirituality included are sense of community, meaningful work and work experience. This is to identify the relationship between those dimensions and organizational commitment, the hypothesis was designed. Questionnaire is used as the method of collecting data. The previous study had been referred to design the questionnaire and the items in the questionnaire had been adapted from the previous study. Proportionate stratified random sampling is the sampling method of this study is. SPSS version 25.0 software is used by the researcher to analyze the primary data and test the hypothesis. Correlation test had been used in this research in order to test the relationship between variables. The findings indicate that sense of community and meaningful work significantly related to the organizational commitment. Regression test is used by the researcher to test the model fit. In this study also includes the discussion of the research objectives and recommendations for the organization and future research.